Do proton pump inhibitors alter the response to immune checkpoint inhibitors in cancer patients? A meta-analysis - Lopes, Sébastien; Pabst, Lucile; Dory, Anne; Klotz, Marion; Gourieux, Bénédicte; Michel, Bruno; Mascaux, Céline (Frontiers in Immunology, 2023)
Introduction: Gut microbiota can significantly affect the effectiveness of immune checkpoint inhibitors (ICIs) in cancer patients. Recently, antibiotics were shown to decrease survival rate of patients treated by ICIs. Proton pump inhibitors (PPIs) can indeed modulate microbiota’s diversity, therefore altering ICIs response. A meta-analysis was performed based on published data to verify this hypothesis. Methods: In this study, over 41 publications, exploring the impact of concomitant PPIs treatment on outcomes of ICIs treated patients, were analyzed. Evaluated endpoints were overall survival (OS) and progression-free survival (PFS). Pooled hazard ratios (HRs) with a 95% confidence interval (CI) were reported in ICIs in PPI users versus non-PPI users. Subgroup analyses were performed to minimize the impact of studies heterogeneity and to investigate the influence of PPI on the different groups of interest. There was no evidence of publication bias for OS and PFS analysis in subgroup analysis. Results: Forty-one studies were included in the meta-analysis, including a total of 20 042 patients. OS of patients receiving ICIS was negatively correlated in patients concomitantly treated with (HR=1.37, 95% CI: 1.23-1.52). PFS of cancer patients receiving ICIs was also negatively correlated with PPI treatment (HR=1.28, 95%CI 1.15-1.42). PPI and ICI use was associated with worst OS and PFS for non-small-cell lung cancer (NSCLC) or urothelial cancer patients, but also for patients treated with anti PD-1 (OS) and anti PD-L1 (OS and PFS) immunotherapies when administered in non-first line and when PPIs was received as baseline treatment or in 60 days before ICIs initiation. PPI and ICI use also showed the worst OS and PFS for patients from Europe and Asia. Conclusion: This meta-analysis suggests that PPI treatment leads to significantly worse outcomes in advanced cancer patients treated by ICIs in terms of PFS and OS